1997
DOI: 10.1016/s0194-5998(97)70185-2
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral cavity in patients younger than 40 years

Abstract: Squamous cell carcinoma of the head and neck has been regarded as a disease affecting the elderly. Several etiologic factors have been demonstrated, such as tobacco and alcohol use and premalignant lesions, whereas others have been suspected, such as genetic or immunodeficiency disorders. Recently, some reports have addressed a tendency toward an increase in the incidence of squamous cell carcinoma in young patients. In recent years we have observed an increase in the number of squamous cell carcinomas in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
5
31
1
Order By: Relevance
“…There is a general agreement in the literature of a higher male preponderance of SCC of the OC and OP in young patients [4,15-18]. A male to female ratio of 3.8:1 observed among the young patient group in our study is a bit higher than a few other reports which gave the gender ratio to be 1.6:1 [15], 1.7:1 [4], 1.9:1 [16], and 2.3:1 [17].…”
Section: Discussionmentioning
confidence: 94%
“…There is a general agreement in the literature of a higher male preponderance of SCC of the OC and OP in young patients [4,15-18]. A male to female ratio of 3.8:1 observed among the young patient group in our study is a bit higher than a few other reports which gave the gender ratio to be 1.6:1 [15], 1.7:1 [4], 1.9:1 [16], and 2.3:1 [17].…”
Section: Discussionmentioning
confidence: 94%
“…Finally many patients in this study were smokers and/or drinkers, without data on the duration of the consumption, which is a weakness of this design. However, previous reports on SCCOT in young people focused on those aged 40Á45 years or younger, with a median age close to 40 [3,4,7]. It is obvious that incidence increases quickly after the age of 35 and with the combination of alcohol and cigarette consumption [1].…”
Section: Discussionmentioning
confidence: 99%
“…Literature data on this population are contradictory. While older reports showed a worse evolution in young people [4,5], more recent reports that include adjustment of confounding variables show a similar prognosis to that in older groups [3,6]. This study was undertaken to assess our practice in the management of squamous cell carcinoma (SCC) in a young population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco and alcohol are the major risk factor for head and cancer, but different studies have found a variable and sometimes absent relationship with these traditional risk factors in young patients and in female [5][6][7][8] . These traditional risk factors are also less important in cases of non-SCC of the head and neck.…”
Section: Introductionmentioning
confidence: 99%